Localization of the Cluster satellites in the geospace environment - Grison, Benjamin; Darrouzet, Fabien; Maggiolo, Romain; Hajoš, Mychajlo; Dvořák, Michal; Švanda, Martin; Jeřábková, Anna; Taylor, Matthew Graham George Thaddeus; Herment, Delphine; Masson, Arnaud; Souček, Jan; Santolík, Ondřej; et al. (Scientific data, 2025)
The geometry of the terrestrial magnetized environment, or geospace, varies widely in space and time due to the Earth's magnetic field interactions with the interplanetary medium. A spacecraft's location in geospace is only approximately determined by its coordinates since the environment is inhomogeneous, with distinct physical processes occurring in different regions. Knowing the location in the geospace offers a strong support for data analysis. This paper introduces a new dataset, Geospace Region and Magnetospheric Boundary identification (GRMB), which provides labelled positions for each Cluster spacecraft over the whole mission, with respect to the local environment. This continuous labelling is based on manual selection, supported by browsing 44 different Cluster data products. The GRMB dataset includes 15 labels spanning from the plasmasphere to solar wind regions. Its consistency is validated over 7 years against reference lists and by the physical properties of the GRMB regions. Over those years, Cluster spent a similar proportion of the time (≈15%) in the regions labelled lobe, plasmasheet, plasmasheet transition region, magnetosheath and solar wind.